The Economic Consequences of Gray Divorce for Women and Men. (9th September 2020) - Lin, I-Fen; Brown, Susan L
Abstract: Objectives: Gray divorce, which describes divorce among persons aged 50 and older, is increasingly common reflecting the doubling of the gray divorce rate since 1990. Yet, surprisingly little is known about the consequences of gray divorce and in particular how women and men fare economically during the aftermath. Method: Using longitudinal data from the 2004–2014 Health and Retirement Study, we estimated hybrid fixed/random-effects models comparing women's and men's economic well-being prior to, during, and following gray divorce and subsequent repartnering. Results: Women experienced a 45% decline in their standard of living (measured by an income-to-needs ratio), whereas men's dropped by just 21%. These declines persisted over time for men, and only reversed for women following repartnering, which essentially offset women's losses associated with gray divorce. No gender gap emerged for changes in wealth following divorce with both women and men experiencing roughly a 50% drop. Similarly, repartnering was ameliorative only for women's wealth. Discussion: Gray divorce is often financially devastating, especially for women. Although repartnering seems to reverse most of the economic costs of gray divorce for women, few form new co-residential unions after divorce. This study offers a cautionary tale about the financial aftermath of gray divorce, which is likely to contribute to growing economic disadvantage among older adults.